Hepatitis B Virus Exploits ERGIC-53 in Conjunction with COPII to Exit Cells - Zeyen, Lisa (Cells, 2020)
Several decades after its discovery, the hepatitis B virus (HBV) still displays one of the most successful pathogens in human populations worldwide. The identification and characterization of interactions between cellular and pathogenic components are essential for the development of antiviral treatments. Due to its small-sized genome, HBV highly depends on cellular functions to produce and export progeny particles. Deploying biochemical-silencing methods and molecular interaction studies in HBV-expressing liver cells, we herein identified the cellular ERGIC-53, a high-mannose-specific lectin, and distinct components of the endoplasmic reticulum (ER) export machinery COPII as crucial factors of viral trafficking and egress. Whereas the COPII subunits Sec24A, Sec23B and Sar1 are needed for both viral and subviral HBV particle exit, ERGIC-53 appears as an exclusive element of viral particle propagation, therefore interacting with the N146-glycan of the HBV envelope in a productive manner. Cell-imaging studies pointed to ER-derived, subcellular compartments where HBV assembly initiates. Moreover, our findings provide evidence that HBV exploits the functions of ERGIC-53 and Sec24A after the envelopment of nucleocapsids at these compartments in conjunction with endosomal sorting complexes required for transport (ESCRT) components. These data reveal novel insights into HBV assembly and trafficking, illustrating therapeutic prospects for intervening with the viral life cycle.